PELAKSANAAN MANAJEMEN TK AN NAMIROH PUSAT DALAM MENINGKATKAN KUALITAS SEKOLAH DI KECAMATAN TAMPAN KOTA PEKANBARU - Yenda Puspita; Hadriana Hadriana; Rusdi Rusdi (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2021)
This study aims to obtain about the process of implementation of kindergarten An-Namiroh Center in improving the quality of schools in Kecamatan Tampan kota pekanbaru. The research sub-focus consists of 1) .The implementation of An-Namiroh kindergarten planning in improving the quality of schools in Kecamatan Tampan Pekanbaru City, 2) .The implementation of An-Namiroh kindergartensCenter in improving the quality of schools in Kecamatan Tampan Pekanbaru City, 3) .The implementation of TK An -Namiroh Center in improving the quality of schools in Kecamatan Tampan Pekanbaru City, 4) .TK An-Namiroh kindergarten supervisionCenter in improving the quality of schools in Kecamatan Tampan Pekanbaru City. This type of research is a qualitative research. The data collection is done by interview, observation and documentation. The results of this study are (1). Implementation of TK An Namiroh Center planning as stipulated in the vision, mission and objectives that make kindergarten An Namiroh Center of pilot educational institutions and is the pride of the community. (2). Implementation of organizing is contained in the organizational structure and the division of labor, so that tasks and responsibilities are done well. (3). Implementation of the guidance of kindergarten An Namiroh Center well done, this is marked by the implementation of leadership functions of principals who have done the management and school construction through administrative activities and placing himself as a supervisor. (4). Implementation of supervision in kindergarten An Namiroh Center has been going well. This is marked by the establishment of good cooperation between the chairman of the foundation, principals, teachers and education personnel as well as the evaluation of weekly performance carried out by the principa